Analisis Konsep dan Dasar Keuangan Islam - Fany Renaldy Harahap; Anggia Nurulita; Adelia Fitra Gustari; Syarah Nurul Fhadhilah Hrp; Padlan Soleh; Chelsea Sakira; Yusrizal Yusrizal (Universitas Muhammadiyah Enrekang, 2022)
The Islamic financial system is a system that deals with finance and connects individuals who need and have excess wealth from Islamic-based financial products and services. The purpose of this study is to teach the basic concepts of Islamic finance. The survey approach used is qualitative. The literature study used was trying to collect data and information by using various reading materials found from various books, magazines, documents, memos, and historical anecdotes related to the research. To have a greater impact on the economy, the Islamic financial system must have a more significant portion of total financial assets, which is at least 20 percent. Therefore, the government, central bank, and business people working on the Islamic financial system must work harder.